Electric Arc Furnace Dust Vitrification via Soda Lime Recycled Glass - Andronikos Maris; Dimitra Ioannidou; Ilias Sammas; Stavros Deligiannis; Petros E. Tsakiridis (Materials Proceedings, 2023)
The present research work focuses on the characterization and leachability evaluation of electric arc furnace dust (EAFD) and its vitreous outgrowths produced during vitrification with soda lime recycled glass (SLRG). EAFD is a hazardous industrial waste generated in the collection of particulate material during the steelmaking process via an electric arc furnace. Glasses of various syntheses were obtained during EAFD vitrification with various amounts of silica scrap (50, 60 and 70 wt%). The characterization of the as-received dust was carried out by using granulometry analysis, chemical analysis, X-ray diffraction (XRD), and scanning electron microscopy (SEM), in conjunction with Energy Dispersive X-ray Spectroscopy (EDS). The produced glasses during vitrification were studied by means of chemical and mineralogical analysis, whereas their microstructure in polished sections was examined by SEM/EDS. Their behavior during leaching was determined by the EN 12457-2 compliance leaching test and according to the results, the trace elements detected in the leachates were well below the corresponding regulatory limits.